Impact of vaccination policy on changes in rubella virus antibody in Japanese pregnant women - Hanaoka, M.; Yamaguchi, K.; Yamaguchi, S. (Journal of Public Health, 2022)
Aim As a result of the 2012–2013 rubella epidemics in Japan, many cases of congenital rubella syndrome have been reported. Given the frequent changes to rubella vaccination policy in Japan, we investigated antibody prevalence among pregnant women according to birth year. Subjects and methods Participants comprised 55,400 pregnant Japanese women for whom rubella-specific hemagglutination inhibition antibody had been measured during early pregnancy in our institute from 1987 to 2016. Birth year was considered for the 47,978 cases for which age was known. Results The ratio of rubella antibody-negative cases among pregnant women born after 1962 decreased significantly with mandatory vaccination. In the transition phase, during which the administration target was changed from schoolgirls to children of both sexes (born 1979–1987) as temporary vaccination, the ratio of rubella antibody-negative pregnant women started increasing in the latter period of this phase. For generations born in or after 1988, the ratio of rubella antibody-negative pregnant women clearly increased when the vaccination target changed to non-mandatory vaccination of children of both sexes. Conclusions Prevalence of antibody titers depends on vaccine coverage rates. Suitable information needs to be provided prior to conception to all women, their husbands, and family members.